Functional form for United States-Mexico trade equations - Fullerton Jr., Thomas M.; Charles Sawyer, W.; Sprinkle, Richard L. (Estudios Económicos de El Colegio de México, 1997)
The literature concerning bilateral trade flows between Mexico and the United States is comparatively small. With the growing importance of international commerce between these economies, potential trade flow responses to changes in relative prices and income performance deserves more attention. This paper attempts to partially fill this gap in the literature by estimating bilateral trade flow equations that decompose relative import and relative export prices into foreign prices, domestic prices, and the exchange rate.